IS THERE A DUTY TO RESPECT "HISTORICAL" FAITH? CHRISTIAN PROSELYTISM OF AN OLDER JEWISH WOMAN WITH DEMENTIA. Issue 2 (20th June 2016) - Doron, Israel (Issi); Foster, Charles
Abstract: In this article, we present a short case study based on an incident that occurred in Israel several years ago. The incident did not reach the courts but was made public by the family members of the older woman at the center of it. The family argued that the actions taken by one of the parties involved should have been defined as elder abuse, but no criminal charges were ever brought. Yet the issues concern key legal and ethical questions about law, religion, and older persons. More specifically, the incident raises the issue of the moral commitment to one's past religious beliefs in reference to one's current choices and preferences once living with dementia. We contend in this article that an Aristotelean account of human dignity would have provided the most satisfactory way to resolve the tensions created by this incident.